2018
DOI: 10.4049/jimmunol.1800396
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Effector and Resident Memory T Cell Generation during Pediatric Viral Respiratory Tract Infection

Abstract: Viral respiratory tract infections (VRTI) remain a leading cause of morbidity and mortality among infants and young children. In mice, optimal protection to VRTI is mediated by recruitment of effector T cells to the lungs and respiratory tract, and subsequent establishment of tissue resident memory T cells (Trm), which provide long-term protection. These critical processes of T cell recruitment to the respiratory tract, their role in disease pathogenesis, and establishment of local protective immunity remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
(59 reference statements)
2
30
0
Order By: Relevance
“…The majority of these tissue memory cells comprise noncirculating T RM cells that exhibit distinct phenotypic and transcriptional profiles that enable their retention in tissue sites ( Hombrink et al., 2016 ; Kumar et al., 2017 ); tissue-specific proportions of T RM in each site are stably maintained with age ( Senda et al., 2019 ; Thome et al., 2014 ). Given that T RM are formed early in life and can be detected in mucosal sites in infants and children and during an active infection ( Connors et al., 2018 ; Thome et al., 2016a ), it is possible that T RM maintain long-term immunity for maintenance of tissue homeostasis.…”
Section: Immunity In Space and Timementioning
confidence: 99%
“…The majority of these tissue memory cells comprise noncirculating T RM cells that exhibit distinct phenotypic and transcriptional profiles that enable their retention in tissue sites ( Hombrink et al., 2016 ; Kumar et al., 2017 ); tissue-specific proportions of T RM in each site are stably maintained with age ( Senda et al., 2019 ; Thome et al., 2014 ). Given that T RM are formed early in life and can be detected in mucosal sites in infants and children and during an active infection ( Connors et al., 2018 ; Thome et al., 2016a ), it is possible that T RM maintain long-term immunity for maintenance of tissue homeostasis.…”
Section: Immunity In Space and Timementioning
confidence: 99%
“…Samples collected from the upper respiratory tract and lower respiratory tract from human infants infected with a respiratory virus demonstrate a propensity toward expansion of terminally differentiated effector cells and reduced mature tissue resident memory (TRM) formation based on CD103 expression . This increased effector T‐cell infiltration is associated with lung injury . Two‐week old mice infected with influenza virus demonstrate comparable numbers of viral‐specific CD8 + T cells in the lungs at day 12–15 postinfection adult mice .…”
Section: Cd8+ T‐cell Function In Viral Infectionsmentioning
confidence: 99%
“…119 This increased effector T-cell infiltration is associated with lung injury. 119 Two-week old mice infected with influenza virus demonstrate comparable numbers of viral-specific CD8 + T cells in the lungs at day 12-15 postinfection adult mice. 120 Despite the prevalence of the viralspecific CD8 + T cells during acute infection, mice infected at 2 weeks of age have reduced TRM in adulthood, and, more importantly, this reduced TRM population provides less protection compared to adults rechallenged with a heterosubtypic virus mice.…”
Section: Cd8 + T-cell Function In Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling of the airway by these methods typically results in limited cell yields and the cells that are recovered are generally highly enriched for granulocytes, complicating detailed characterisation of less abundant phenotypes using traditional flow cytometry-based tools 8 . Recent analysis of the cellular composition of upper airway by flow cytometry showed that the typical abundances of critical effector cells like T Cells, B Cells, Mast cells, Dendritic cells and NK cells to be less than 0.5% of all airway cells, while granulocytes were present at a median frequency of >90% 9 .…”
Section: Introductionmentioning
confidence: 99%